Plastic deformation of Mg17Al12 at 25–250 °C – properties and dislocation mechanisms - Martina Freund; Zhuocheng Xie; Markus Kolb; Pei-Ling Sun; Marcus Hans; Jeffrey M. Wheeler; Sandra Korte-Kerzel (Materials & Design)
Mg17Al12 is a well-known precipitation phase in magnesium alloys containing aluminium. Although its low-temperature deformation mechanisms remain insufficiently understood, Mg17Al12 is known to co-deform with the hexagonal magnesium matrix under high stress at low temperatures and to soften above 150 °C, thereby losing its reinforcing capability in magnesium alloys. In this work, we employ nanoindentation and micropillar compression to explore not only the mechanical properties of Mg17Al12 but also its underlying dislocation motion mechanisms. A pronounced reduction in yield stress occurs at and above 150 °C, accompanied by the disappearance of serrated plastic flow shown at lower temperatures and a more homogeneous flow manifested by the absence of surface slip traces. First data from atom probe tomography suggests that the observed serrations may arise from Al segregation to dislocations. We find that Mg17Al12 deforms on {110} planes and identify 〈11¯1〉 type Burgers vectors by transmission electron microscopy. Through atomistic simulations, we substantiate these results are substantiated by investigation of the possible slip planes, paths, and energy barriers and contrast the findings on Mg17Al12 with the mechanisms observed in the isostructural α-Mn.